Artificial intelligence for precision medicine in autoimmune liver disease - Gerussi, Alessio; Scaravaglio, Miki; Cristoferi, Laura; Verda, Damiano; Milani, Chiara; De Bernardi, Elisabetta; Ippolito, Davide; Asselta, Rosanna; Invernizzi, Pietro; Kather, Jakob Nikolas; Carbone, Marco (Frontiers in Immunology, 2022)
Autoimmune liver diseases (AiLDs) are rare autoimmune conditions of the liver and the biliary tree with unknown etiology and limited treatment options. AiLDs are inherently characterized by a high degree of complexity, which poses great challenges in understanding their etiopathogenesis, developing novel biomarkers and risk-stratification tools and, eventually, generating new drugs. Artificial intelligence (AI) is considered one of the best candidates to support researchers and clinicians in making sense of biological complexity. However, the applications of AI in human diseases may present several hurdles related to data extraction from electronic health records and digital images (either radiological or pathological) and their integration with biological data derived from high-throughput technologies. In this review, we offer a primer on AI and Machine Learning for clinicians, discuss recent available literature on its applications in medicine and more specifically how it can help to tackle major unmet needs in AiLDs.